The Role of Clusterin (CLU) in the Pathogenesis of Benign Prostatic Hyperplasia: Mechanisms and Potential as a Biomarker: Peran Clusterin (CLU) dalam Patogenesis Hiperplasia Prostat Jinak: Mekanisme dan Potensi sebagai Biomarker - Reza, Muhammad Alfi; Krisna, Muhammad Sidharta; Diennillah, Fathannia Rizky; Putri, Jihan Asma; Yulianto, Andy (Journal of Aafiyah Health Research (JAHR), 2024)
ABSTRACT Background: Benign Prostatic Hyperplasia (BPH) is a common urological condition characterized by excessive proliferation of prostate epithelial and stromal cells, leading to lower urinary tract symptoms. Clusterin (CLU), a multifunctional glycoprotein, has been implicated in various cellular processes, including apoptosis regulation, inflammation, and autophagy. However, its exact role in BPH pathogenesis remains unclear. Objective: This study aims to analyze the role of CLU in the molecular mechanisms underlying BPH and evaluate its potential as a biomarker for disease progression. Method: A comprehensive analysis of recent literature was conducted to examine CLU expression in BPH tissues and its interactions with inflammatory pathways, hormonal regulation, and cellular homeostasis mechanisms such as apoptosis and autophagy. The study also reviewed CLU’s involvement in epithelial-stromal interactions and its correlation with disease severity. Results: Increased CLU expression in hyperplastic prostate tissues is associated with chronic inflammation, contributing to aberrant cell proliferation and apoptosis resistance. CLU interacts with inflammatory markers such as TNF-α and IL-6, promoting a microenvironment conducive to disease progression. Additionally, CLU is involved in autophagy dysregulation, which may further sustain cellular survival and resistance to apoptosis. Evidence suggests that hormonal factors, particularly androgens and estrogens, regulate CLU expression, linking it to prostate tissue remodeling. These findings highlight CLU as a potential biomarker for assessing BPH severity and progression. Conclusion: CLU plays a critical role in BPH pathogenesis by modulating inflammatory responses, apoptosis, and cellular homeostasis. Its increased expression in hyperplastic prostate tissues suggests that it may serve as a novel biomarker for disease progression. However, further studies are needed to validate its clinical applicability and explore targeted therapies aimed at CLU modulation to improve BPH management.